Preliminary identification of beta-hemolytic streptococci in throat swab cultures with a commercial blood agar slide (streptocult). - Christensen, P (1982)
A commercial blood agar slide (Streptocult, Orion Diagnostica) was used for preliminary identification of beta-hemolytic streptococci of groups A, C, and G in throat swab specimens. The sensitivity of the test was 93.6% and the specificity was 94.7%, as judged from 580 specimens. A model is suggested for routine processing of throat swab specimens, involving inoculation and reading of the slide in general practice and transport of positive or inconclusive slides to a bacteriology laboratory for isolation and serological grouping of beta-hemolytic streptococci. The model combines preliminary detection of beta-hemolytic streptococci within 24 h with the reliability of serological groupings, and should reduce the volume of specimens sent to the laboratory considerably.